The role of artificial intelligence in transforming human resource practices: Quantitative evidence from the Saudi telecom companies - Albaqami, Adi Sudan (Edelweiss Applied Science and Technology, 2025)
The rapid development of high technology has compelled many organizations to continuously seek new concepts, ideas, tests, and innovative solutions to improve their current technology, systems, processes, and products. Artificial intelligence (AI) is increasingly utilized by modern businesses to foster a more profitable and successful future. Integrating AI-powered solutions into human resource (HR) practices offers significant potential, especially as Saudi Arabia endeavors to meet the demands of economic diversification, transformation into a knowledge-based economy, and enhancement of societal well-being. This paper aims to examine the role of AI in transforming HR practices within Saudi telecom companies. The study focused on four HR practices: training and development, performance management, employee engagement, and selective hiring. A quantitative approach was employed, involving the design and distribution of a questionnaire to a sample of 130 managers working in Saudi telecom companies. The findings indicate that AI plays a substantial role in improving HR practices in these companies. Among the practices, selective hiring is most influenced by AI, followed by training and development, then performance management, and finally employee engagement. Based on these results, it is recommended that Saudi telecom companies develop a database utilizing AI to enhance the efficiency and quality of HR services and activities. Furthermore, these companies should address the challenges associated with AI implementation and ensure that the technology is applied ethically and equitably.